Safety analysis of zolpidem in elderly subjects 80 years of age or older: adverse event monitoring in Japanese subjects. (2nd June 2016) - Kajiwara, Ayami; Yamamura, Masato; Murase, Motoji; Koda, Haruo; Hirota, Seisuke; Ishizuka, Tadao; Morita, Kazunori; Oniki, Kentaro; Saruwatari, Junji; Nakagawa, Kazuko
Abstract : Objectives: Prescriptions of non-benzodiazepine sedative hypnotics, e.g. zolpidem, for insomnia in elderly subjects 80 years of age or older have markedly increased in the USA. However, a meta-analysis of the risks and benefits of hypnotics in older people reported the benefits associated with hypnotics use are outweighed by the risks. This study aimed to investigate the safety of zolpidem administration in extremely old elderly. Methods: The prevalence of adverse reactions to zolpidem was investigated in a subpopulation of participants in the Drug Event Monitoring project of the Japan Pharmaceutical Association. A total of 1011 (316 males and 695 females) zolpidem users, including 261 (25.8%) subjects 80 years of age or older without cognitive or mental complications, were eligible for the analysis. Results : The elderly and female patients were prescribed significantly lower doses of zolpidem than their counterparts. Adverse symptoms after the last prescription were reported by 60 (5.9%) subjects. The most common symptoms were impaired balance and/or falls (1.8%) and morning drowsiness (1.3%). The multiple logistic regression analyses showed that subjects 80 years of age or older were at lower risk of adverse symptoms (odds ratio 0.39, 95% confidence intervals: 0.17–0.88). Conclusion : Our findings in a real-world clinical setting suggest that low-dose zolpidem can be safely prescribed to subjects 80 years of age or older without cognitive or mental complications.